Evaluation of asymptomatic venous disease by venous Doppler ultrasonography in patients with Behcet's disease without overt thrombosis - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (SPRINGER LONDON LTD, 2014)
One of the major causes of mortality and morbidity in Behcet's disease (BD) is vascular involvement. Limited data suggest a high prevalence of venous insufficiency (VI) and some cases of asymptomatic thrombosis in BD. In this study, we aimed to investigate asymptomatic venous disease by venous Doppler ultrasonography (US) prospectively in patients with BD, without known vascular disease. The study included 93 patients with BD (M/F, 45/48; age, 36.4 +/- 10 years), 97 patients with ankylosing spondylitis (AS) (M/F, 50/47; age, 37.5 +/- 9.5 years), and 43 healthy controls (HC) (M/F, 25/18; age, 34.7 +/- 4.5 years). All patients were examined for the clinical findings of venous thrombosis. Vessels of both upper and lower extremities were examined, while the subjects were in supine position by venous Doppler US. Clinical signs (C), the various etiologies (E), anatomical sites (A), and pathophysiological disorder (P) (CEAP) severity score was used to evaluate the severity of the VI. We did not detect any silent thrombosis in any group. VI findings in lower extremity were detected in 32.2 % (n = 30) in the BD group, 28.8 % (n = 28) in AS group, and 9.3 % (n = 4) in the HC group. Both BD and AS patients had significantly higher VI rates than controls (p = 0.007 and 0.015). Similarly, CEAP severity score in BD (0.34 (0-3)) was significantly higher than controls (0, p = 0.008) but similar to AS (0.18 (0-39), p = 0.18). No correlations were present between C-reactive protein elevation (> 5 mg/L) and VI in both BD (p = 0.546) and AS (p = 0.754). A high prevalence of VI was present in both BD and AS patients without symptomatic thrombosis. Presence of VI also in AS, a disease without a major tendency to venous thrombosis, might suggest that chronic inflammation might cause a mild insufficiency detected only by Power US in venous vessels. Long-term consequences of this finding require further follow-up studies to show whether asymptomatic venous disease is a predictor of future venous thrombotic events in patients with BD.
Keywords: Asymptomatic; Behcet's disease; Venous insufficiency; MANAGEMENT; MORTALITY; CRITERIA